2008
DOI: 10.1590/s0004-27302008000600008
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes and pre-eclampsia: common antecedents?

Abstract: Objetivo: Avaliar a concordância do padrão de fatores de risco de mulheres que desenvolvem diabetes gestacional e pré-eclâmpsia. Métodos: Estudo de coorte prospectivo em clínicas de atendimento pré-natal do Sistema Único de Saúde de seis capitais do Brasil, 4.766 mulheres grávidas de 20 a 48 anos de idade foram arroladas de maneira consecutiva entre a 20º e 28º semanas de gestação. O hábito de fumar e os fatores de risco tradicionais para pré-eclâmp-sia e diabetes gestacional foram obtidos por entrevista no ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
1
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 60 publications
(46 reference statements)
5
33
1
10
Order By: Relevance
“…Abnormalities of pregnancy appear to be common among patients with trisomy 18, which can lead to complications for both the fetus and the mother. In our study we found that preeclampsia was found in 17% of pregnancies of the patients, a rate higher than that observed in Brazil, which ranges around 2-3% (2-10% worldwide) [WHO, 1988;Gaio et al, 2001;Wendland et al, 2008]. What caught our attention is the fact that the other study with Brazilian patients with trisomy 18, by Sugayama et al [1999], described an index of unspecified hypertension in pregnancy of 25%.…”
Section: Discussionmentioning
confidence: 48%
“…Abnormalities of pregnancy appear to be common among patients with trisomy 18, which can lead to complications for both the fetus and the mother. In our study we found that preeclampsia was found in 17% of pregnancies of the patients, a rate higher than that observed in Brazil, which ranges around 2-3% (2-10% worldwide) [WHO, 1988;Gaio et al, 2001;Wendland et al, 2008]. What caught our attention is the fact that the other study with Brazilian patients with trisomy 18, by Sugayama et al [1999], described an index of unspecified hypertension in pregnancy of 25%.…”
Section: Discussionmentioning
confidence: 48%
“…Consistent with previous reports, although PE and GDM have distinctive clinical and pathophysiologic characteristics, they share some important similarities: both conditions develop during pregnancy, and the clinical syndromes disappear after delivery. Many risk factors such as obesity, elevated blood pressure, dyslipidemia, insulin resistance, and hyperglycemia are associated with both PE and GDM; and patients with a history of PE or GDM have increased risk of developing cardiovascular disease compared to women without such a history [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22]. …”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiologies of both illnesses have been shown to be associated with each other [3,4,5,6]. It appears that gestational diabetes and pre-eclampsia have several mechanisms in common: altered carbohydrate metabolism causes vascular changes such as arteriosclerosis and a glomerular filtration dysfunction, which results in a predisposition to pre-eclampsia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential mediating role of weight trajectories was examined in a supplemental analysis examining weight change from age 18 years to prepregnancy. Finally, the authors ran a supplemental analysis of mediation by prepregnancy smoking, which is common after abuse 29 and may be associated with GDM 30,31 ; prepregnancy smoking was defined as current smoking reported on the biennial questionnaire prior to the pregnancy.…”
Section: Methodsmentioning
confidence: 99%